Construction of optical solitons of magneto-optic waveguides with anti-cubic law nonlinearity - Asjad, Muhammad Imran; Ullah, Naeem; Rehman, Hamood Ur; İnç, Mustafa (Springer, 2021)
Two efficient integration schemes, new extended hyperbolic function and generalized tanh are employed to discover optical soliton solutions to magneto-optic waveguides that retains anti-cubic form of nonlinear refractive index. Bright, dark, periodic singular, singular, and combo soliton solutions have created. These solutions expose the comprehensive variety of soliton solutions.
Keywords: Magneto-optic waveguides with anti-cubic law nonlinearity; New extended hyperbolic function method; Tanh method; Optical soliton solutions